High-resolution precipitation simulation with WRF for the Three-River Headwaters region in China. Issue 1 (December 2020) - Li, X D; Wang, Y Q; Tian, L; Xu, J J; Qu, S M; Wei, F C; Pan, X
Abstract: The Three-River Headwater Region (TRHR), also known as China "Water Tower". It is a sensitive region to climate change and plays a critical role in the hydrology circulation and ecological conservation of the Tibet Plateau. Climate change are greatly impacting the climate of this region. However, there exists large biases in the precipitation simulation for this region. In this study, we explored the impact of resolution and physical schemes on precipitation simulation over the TRHR. The results show that a high resolution is necessary for the precipitation modelling over the TRHR with a complex terrain. The precipitation modelling over the TRHR are sensitive to microphysics schemes and cumulus schemes. The microphysics scheme mainly determines the magnitude of simulated precipitation over the TRHR. The cumulus schemes largely influence the spatial distribution of simulated precipitation over the TRHR. Based on the sensitivity tests, we proposed an optimized combination of parameterization schemes that can remarkably improve the accuracy of simulated precipitation over the TRHR. This study is helpful to understand the mechanism of precipitation formation over the TRHR.